Social isolation in mice: behavior, immunity, and tumor growth. (4th March 2021) - Farbstein, Dan; Hollander, Nurit; Peled, Orit; Apter, Alan; Fennig, Silvana; Haberman, Yael; Gitman, Hila; Yaniv, Isaac; Shkalim, Vered; Pick, Chaim G.; Benaroya-Milshtein, Noa
Abstract: The aim of this study was to investigate the behavioral, immunological, and neurological effects of long-term isolation in an animal model. Male C3H/eB mice wereraised in either social isolation or standard conditions for 6 weeks. At 10 weeks, each group was further divided into 3 sets. (A) Physical strength and behavior were evaluated with the grip strength, hot plate, staircase, and elevated plus-maze tests. Natural-killer cell activity and lymphocyte proliferation were measured. (B) Half the animals were subjected to electric shock with 3 reminders, and freezing time was evaluated at each reminder. Cortisone levels were evaluated after 16 weeks. (C)Mice were injected with 38 C-13 B lymphoma cells and followed for tumor size and survival. Strength evaluation yielded asignificantly lower body weight and grip strength in the socially isolated mice. Behavioral test results were similar in the two groups. The pattern of reactions to stress conditioning differed significantly, with the socially isolated mice showing an incline in freezing with each successive reminder, and the control mice showing a decline. The socially isolated mice had significantly attenuated tumor growth, with no significant difference in survival from control mice. There were no significant between-group differences in immunological parameters. In conclusion, social isolation serves as a model for chronic stress. It was associated with significant changes in stress conditioning reaction, resembling symptoms of post-traumatic stress disorder, and attenuated tumor development. No differences from controls were found in behavior tests, immune parameters, or survival after tumor cell inoculation. Lay summary: This article explores biological and behavioral consequences of social isolation in a mice model. Our results show that social isolation leads to changes in the Hypothalamic-hypophyseal-adrenal axis, which in turn alter the response to stress. Additionally, social isolation was shown to impact tumor progression.